Frequency and determinants of thyroid autoimmunity in Ghanaian type 2 diabetes patients: a case-control study. Issue 1 (December 2017) - Sarfo-Kantanka, Osei; Sarfo, Fred; Ansah, Eunice; Yorke, Ernest; Akpalu, Josephine; Nkum, Bernard; Eghan, Benjamin
Abstract Background The link between type 1 diabetes and thyroid autoimmunity is well described. The same cannot be said for type 2 diabetes where results have been mixed so far. We investigated the prevalence and determinants of thyroid autoimmunity among Ghanaian type 2 diabetes patients. Methods This was a case-control study involving 302 type 2 diabetes patients and 310 non - diabetic controls aged 40–80 years. Anthropometric and blood pressure measurements were obtained. Fasting samples were analyzed for glucose, thyroid function, and antibodies to thyroglobulin and thyroid peroxidase. Results The prevalence of thyroid autoimmunity was significantly higher among T2DM subjects (12.2% vs. 3.9%, p  = 0.0004). Among T2DM subjects, 44 (14.7%) tested positive for TPOAb, 5 (1.7%) tested positive for TGAb and 15 (5.0%) tested positive for both autoantibodies. Females T2DM subjects showed a 3-fold increased risk of thyroid autoimmunity compared to males (OR:3.16, p =0.004), T2DM subjects with hyperthyroidism had a 41% increased risk of thyroid autoimmunity (OR: 1.41, p  < 0.001), sub-clinical hyperthyroidism increased the risk of thyroid autoimmunity by 2 fold, (OR:2.19, p  < 0.001), subclinical hypothyroidism increased the risk of autoimmunity by 4-fold, (OR:3.57 95%p  < 0.0001), and hypothyroidism was associated with a 61% increased risk of thyroid autoimmunity (OR: 1.61, 1.35–2.23). Dyslipidaemia was associated with a 44% increased risk of thyroid autoimmunity (OR: 1.44, p  = 0.01) and a percentage increase in HbA1c was associated with 46% increased risk of thyroid autoimmunity (OR:1.46, p  < 0.0001). Conclusion We observed a high prevalence of thyroid autoimmunity in Ghanaian T2DM subjects compared to the general population. Thyroid autoimmunity in T2DM subjects was significantly associated with female gender, thyroid dysfunction, dyslipidaemia and poor glycemic control.